Anomie, irritation, and happiness in the Chilean society post-social outbreak - Moyano-Díaz, Emilio; Palomo-Vélez, Gonzalo; Olivos-Jara, Pablo; Maya-López, Yuxa (Frontiers in Psychology, 2023)
On 18 October 2019, the Chilean people witnessed an unprecedented social outbreak across most of their country. We argue that a state of anomie is a factor associated with the weakening of states, and an anomic state might negatively influence people’s well-being through an increased feeling of irritation. Convenience recruitment via social networks allowed us to form a sample of 194 Chilean participants from the center-south region of the country (M = 36.53 years old, SD = 17.48; 56.7% women). All participants completed testing instruments to measure anomie, irritation, happiness, and political beliefs. Descriptive scores suggest situating Chile in the quadrant of high anomie. Two mediation analyses were conducted. The main results showed a negative indirect effect of the breakdown of the social fabric and leadership on happiness through irritation, although the findings for the former dimension were more robust. Additionally, the breakdown of the social fabric was positively related to the belief that left and right-wing democratic governments are helpless when it comes to fighting delinquency. The breakdown of leadership, on the other hand, was negatively related to political interest. The results should be interpreted with caution due to the limitations of the sample type and the construction validity of some instruments.